2022
DOI: 10.3389/fnmol.2022.855752
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ca2+/Calmodulin-Dependent Protein Kinase Type II in Mediating Function and Dysfunction at Glutamatergic Synapses

Abstract: Glutamatergic synapses harbor abundant amounts of the multifunctional Ca2+/calmodulin-dependent protein kinase type II (CaMKII). Both in the postsynaptic density as well as in the cytosolic compartment of postsynaptic terminals, CaMKII plays major roles. In addition to its Ca2+-stimulated kinase activity, it can also bind to a variety of membrane proteins at the synapse and thus exert spatially restricted activity. The abundance of CaMKII in glutamatergic synapse is akin to scaffolding proteins although its pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 402 publications
0
8
0
Order By: Relevance
“…Intracellular calcium is indispensable for this process [41,42]. Triggered by various stimuli, intracellular calcium overload occurs, which leads to the release of cytochrome C and apoptosis-inducing factors [43]. There is evidence that this is associated with neurodegenerative diseases [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular calcium is indispensable for this process [41,42]. Triggered by various stimuli, intracellular calcium overload occurs, which leads to the release of cytochrome C and apoptosis-inducing factors [43]. There is evidence that this is associated with neurodegenerative diseases [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have indicated that the stimulation of extrasynaptic NMDA receptors containing GluN2B subunits leads to a persistent dephosphorylation of CREB, which is referred to as CREB shut-off [50]. As a result, CREB becomes transcriptionally inactive due to its fast dephosphorylation at serine 133 [51] the result indicates that an increase in Ca 2+ permeable AMPA receptors can initiate NMDA downstream signalling, potentially leading to the activation of the CREB-shut-off pathway in Parkinson's disease. Consequently, this impedes the activation of genes associated with plasticity, such as BDNF, resulting in impaired synaptic function, synapse loss, and eventual cellular death.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, NMDARs, AM-PARs, GABARs, and D2Rs all converge on CaMKII for downstream signal transduction and regulation (re-viewed in [ 10 ]). The beta (regulatory) subunit of CaMKII was found to be upregulated in schizophrenia, both in humans and in an animal model, indicating that it plays an essential role in the disease, likely by increasing the enzyme’s sensitivity to calcium signals [ 88 , 89 , 93 , 156 ]. CaMKII also controls several key phenotypic aspects of schizophrenia, such as enhanced amphetamine-induced dopamine release [ 42 , 94 , 95 , 98 ] and elevated D2High binding states [ 156 ].…”
Section: Discussionmentioning
confidence: 99%
“…In acute stress, CaMKII mediates the response to noradrenaline [ 87 ]. In individuals with increased levels of CaMKIIβ [ 88 , 89 ], this likely results in abnormal reactivity to stress [ 90 ] and dysregulation of the glutamatergic [ 91 ] and dopaminergic [ 82 ] systems (reviewed in [ 10 ]).…”
Section: Molecular Pathways Underlying Schizophrenia Pathologymentioning
confidence: 99%
See 1 more Smart Citation